PRESCHOOL TEACHERS’ CONCERNS ON EDUCATIONAL THEORIES AND VIEWS OF EDUCATIONISTS TO DEVELOP CREATIVITY IN THE TEACHING- LEARNING PROCESS - Munasinghe, D M W (PEOPLE: International Journal of Social Sciences, 2018)
The global attention on research in preschool education has increased and there is an immense motivation in the field of research in Sri Lanka. This research shows that the preschool education is a critical way to introduce and develop all aspects of a child’s development with a focus on creativity. The mixed method design approach was used in this research and a stratified random sample was used to collect data during 2015 and 2016. Questionnaires, Interviews and observations were used to collect data from the selected preschools in the Colombo district, Sri Lanka. Descriptive statistics were used for data analysis.The findings showed that the majority of preschools are run by Non- Government organizations, and the State does operate some preschools. Most of the preschool teachers of Government and Non- Government preschools were not aware of creativity as a learning concept. It was observed that teachers use several methods that did not promote creativity. Preschool teachers mostly provided instructions while trying to keep children quiet in order to manage the classroom. The majority of preschool teachers stated that they faced problems in preparing lessons to develop children’s creativity. In conclusion, it showed that preschool teachers do not have adequate training and knowledge regarding the importance of creativity and its implications for the education of children.Findings of this research are expected to be shared with relevant authorities in order to improve teacher training, curriculum development and further research on preschool education.